(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The philology student`s communicative abilities are characterized in the article. The reseaschers` expierience of this topic are also described. The future students’ psycology features are analized and based concerning experimental research, the philology students` level of communicative abilities are detected at the present stage.